MITE PEST FAUNA OF OKRA AND THEIR MANAGEMENT - PRASAD, RABINDRA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
Field survey conducted in Ranchi region of Jharkhand pertaining to mite pest fauna associated with okra indicated that the crop was infested with four mite species, Tetranychus urticae, T. macfarlanei, T. ludeni and Brevipalpus phoenicis all-round the year except winter season T. urticae appeared as severe mite pest during spring and post rainy season and as extremely severe pest during hot summer months. Acaricidal trials revealed that fenazaquin (0.05%) proved to be the most effective followed by fenazaquin (0.025%), ethion (0.05%), dicofol (0.06%), Vanguard (neem based) 1.0% and Mitex-s (micronised sulphur) applied Q. 0.250 percent in causing higher mortality of the okra mite, T. urticae. The test acaricides caused mite mortality ranging from 80.53 to 95.16 percent based on the overall results. Key words :,